2018
DOI: 10.1155/2018/1246818
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Evidence for Toll-Like Receptor Activation in Sjögren’s Syndrome

Abstract: While the importance of Toll-like receptor (TLR) signaling is well established in many autoimmune diseases, the role of TLR activation in Sjögren's syndrome (SS) is poorly understood. Studies in mice and humans reveal that TLRs are potent mediators of inflammation in SS. TLRs are expressed and functional in salivary tissue, and TLRs in peripheral blood cells of SS patients are also upregulated and hyperresponsive to ligation. In this review, we will detail observations in mouse models regarding the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 112 publications
1
28
0
Order By: Relevance
“…This paradigm is supported by studies of kidney pathoses, as DAMP-mediated recruitment of Th1 and Th17 cells is mediated by TLR2 and TLR4 interactions (60). Since most cells recruited to the salivary tissue express TLRs (8), this may lead to a continuous cycle of unremitting inflammation and further tissue destruction. As tissue breakdown continues, Dcn levels may become elevated systemically, as is observed for the related DAMP biglycan in SLE patients (44), and this may be a mechanism contributing to the systemic disease manifestations observed in pSS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This paradigm is supported by studies of kidney pathoses, as DAMP-mediated recruitment of Th1 and Th17 cells is mediated by TLR2 and TLR4 interactions (60). Since most cells recruited to the salivary tissue express TLRs (8), this may lead to a continuous cycle of unremitting inflammation and further tissue destruction. As tissue breakdown continues, Dcn levels may become elevated systemically, as is observed for the related DAMP biglycan in SLE patients (44), and this may be a mechanism contributing to the systemic disease manifestations observed in pSS.…”
Section: Discussionmentioning
confidence: 94%
“…Salivary gland inflammation is considered a hallmark of the disease (2), although the inciting disease events and pathways that maintain chronic inflammation in this tissue remain unknown. Several studies suggest that activation of innate immunity precedes the adaptive response in pSS (3)(4)(5)(6)(7)(8). However, the specific pathways that lead to disease initiation and progression are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells are known to modulate their miRNA expression upon activation (26). To investigate whether cDC2 activation is associated with downregulation of miR-708 and miR-130a in pSS, cDC2s from HCs were stimulated with ligands for TLR3 and TLR7/8, which are endosomal nucleic acid receptors that are relevant in pSS pathophysiology (27, 28). We observed that upon cell activation with either TLR ligand the expression of both miR-708 and miR-130a was decreased when compared with the unstimulated condition (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, TLR2, TLR3, and TLR4 are expressed on the SGEC membrane [82], and in addition, immunohistochemical analyses of TLR2, 3 and 4 on labial SG tissue from pSS patients confirmed a significantly higher constitutive expression of these receptors, found in SG-infiltrating mononuclear cells as well as acinar cells and ductal SGEC, supporting the intrinsic epithelial activation in pSS [40]. TLR4, in particular, resulted highly expressed specifically in infiltrating mononuclear cells and in ductal and acinar cells [83,84] of pSS SGs, and receptor levels were correlated with the degree of glandular inflammation [83,84]. At the same time, investigations conducted on pSS peripheral blood mononuclear cell (PBMC) confirmed a dysregulation of TLR7, 8 and 9 molecules compared to controls, where TLR7 and 8 recognize single-stranded RNA [85], while TLR9 is activated by un-methylated CpG DNA [86].…”
Section: Toll-like Receptor-mediated Nf-κb Activation In Pssmentioning
confidence: 68%